Levels of Blood Glucose and Total Protein of Repeat Breeding Dairy Cows From Daerah Istimewa Yogyakarta - Dhasia Ramandani; Alfarisa Nururrozi (Jurnal Sain Veteriner, 2015)
Repeat breeding in dairy cows is a reproductive disorder characterized by a length of calving interval.This research was aimed to determine levels of blood glucose and total protein as one of the causes of repeat breeding. This research used ten repeat breeding Friesian Holstein cross breeds at the age of 3-8 years old from Daerah Istimewa Yogyakarta. They have had birth at least once, normal reproductive cycle, and in a healthy condition. Ten ml blood samples of each cow from jugular vein were collected and analyzed at LPPT UGM. Blood glucose and total protein plasm were examined using a photometer Microlab 300 with a spectrophotometer. The data ware analyzed descriptively. The results showed that dairy cows with repeatedbreeding case had lower blood glucose and total protein plasm concentrations than that of the normal. The average concentrations of blood glucose and total protein plasm were 48.58±6.675 mg/dl and 6.815±821 g/dl, respectively.